Relationship between Spotting Incidence and Anxiety in Family Planning Acceptors 3 Monthly Injections in the Praktek Mandiri Bidan Endang Khoirunnisa - Endang Khoirunnisa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Anxiety experienced by family planning injection acceptors tends to occur when there is a menstrual disorder, causing the acceptor's appetite to increase easily, weight gain, acne occurs. This causes women who use family planning injections to become easily depressed, not confident in their appearance. This anxiety is still often complained of by acceptors even though informed choice and informed consent have been made before giving contraception. The purpose of this study is to analyze relationship between spotting incidence and anxiety in family planning acceptors 3 monthly injections in the Praktek Mandiri Bidan Endang Khoirunnisa in Sewon District, Bantul Regency, Daerah Istimewa Yogyakarta, Indonesia. This study used descriptive analytic method with a cross sectional approach. The population in this study are all mothers who became family planning acceptors 3 monthly injections in the Praktek Mandiri Bidan Endang Khoirunnisa in Sewon District, Bantul Regency, Daerah Istimewa Yogyakarta, Indonesia in April 2018 as many as 126 acceptors. The sampling method is purposive sampling. The number of samples or family planning acceptors is 53 acceptors who met the criteria. The data collected comes from the questionnaire. The method of analysis used the chi-square test. The result show that there is a significant relationship between spotting incidence and anxiety in family planning acceptors 3 monthly injections in the Praktek Mandiri Bidan Endang Khoirunnisa.